Performances of cattle and goats in some selected areas of Gaibandha district in Bangladesh (Bangladesh Journal of Animal Science, 2023)
The survey was conducted to represent the livestock production scenario and to know the performances of cattle and goats in few selected rural areas of Gaibandha district. The data on productive and reproductive performances of cattle and goats were collected from 102 household within four selected village under Gobindaganj Upazila of Gaibandha district with a pretested survey questionnaire. The collected data were compiled, tabulated and analyzed by student t test. In the study area, about 59% were indigenous cattle and 41% were crossbred cattle. A total of 113 goats were found in the study area of which 82% belongs to Black Bengal goat and the remaining 18% belongs Jamunapari goat. All the livestock (100%) were managed intensively during the spring and rainy seasons. Similarly, almost all livestock (100%) are confined in shed at night, and 45.9% and 54.09% of the livestock population are confined in shed and paddock at day time, respectively. Artificial insemination (AI) is the preferred breeding method for cattle, whereas goats primarily rely on natural mating. Milk yield and lactation period of cow, and mature body weight of both male and female were significantly (P